McGraw-Hill's 500 college algebra and trigonometry questions : ace your college exams - Schmidt, Philip A. (New York : McGraw-Hill Education, 2013)
Presents five hundred multiple choice algebra and trigonometry questions similar to those featured on college exams, in addition to detailed explanations of right and wrong answers for each question. --
"For college and career success"--Cover.
Keywords: Algebra -- Examinations, questions, etc; Trigonometry -- Examinations, questions, etc; Algebra -- Examinations -- Study guides; Trigonometry -- Examinations -- Study guides; Advanced placement programs (Education) -- Study guides